Heterosexual outbreak of infectious syphilis: epidemiological and ethnographic analysis and implications for control. (1st April 2002) - Patrick, D M; Rekart, M L; Jolly, A; Mak, S; Tyndall, M; Maginley, J; Wong, E; Wong, T; Jones, H; Montgomery, C; Brunham, R C
Abstract : This study describes the epidemiology and ethnography of an outbreak of infectious syphilis in Vancouver, British Columbia. Between 1996 and 1999, British Columbias's rate of infectious syphilis rose from 0.5 to 3.4 per 100 000, with a dense concentration of cases among sex trade workers, their clients, and street-involved people in the downtown eastside area of Vancouver. Sexual networks were imported cases with secondary spread (dyads and triads), large densely connected dendritic networks of sex trade workers and clients, or occasional starburst networks among gay men. Only 232 of 429 partners were documented as having been treated (54% of those named, or 0.9 per case). The geographical and demographic concentration of this outbreak led to consideration of a programme of focused mass treatment with single dose azithromycin.